2021
DOI: 10.1155/2021/3149289
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Social Health Insurance and Its Predictors among Government Employees in Mujja Town, Ethiopia

Abstract: Background. Social health insurance is one of the possible organizational mechanisms for raising and pooling funds to finance health services, private health insurance, community insurance, and others. Objective. The study was aimed to assess willingness to pay for social health insurance and associated factors among government employees in Mujja town, Ethiopia. Methods. An institutional-based cross-sectional study was conducted on the total sample size of 375 study respondents. A simple random sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
2
8
2
Order By: Relevance
“…This study showed that overall willingness to pay 3% of their monthly salary for SHI was 74.3% which was comparable with study among health professionals in government hospitals, Mekelle City (74.9%) [26] and among teachers in Wolaita Sodo Town (74.4%) [31]. The willingness to pay for SHI found higher than study among health care providers in Addis Ababa (28.7%) [34], among government-owned company employees in Northwest Ethiopia (32%) [27], among government employees in Mujja Town (37.6%) [30] and among civil servants' in Northwest Ethiopia (66.6%) [32]. But it found lower than the willingness and ability to pay for SHI in Nigeria (82%) [35] and among public servants in Mekelle City, Northern Ethiopia (85.3%) [24] In the nal multivariable logistic regression model, respondents who had higher educational level were 5.48(AOR = 5.48; 95% CI: 1.80, 16.73) times more likely to be willing to pay for SHI as compared to those teachers who were rst and diploma holders.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study showed that overall willingness to pay 3% of their monthly salary for SHI was 74.3% which was comparable with study among health professionals in government hospitals, Mekelle City (74.9%) [26] and among teachers in Wolaita Sodo Town (74.4%) [31]. The willingness to pay for SHI found higher than study among health care providers in Addis Ababa (28.7%) [34], among government-owned company employees in Northwest Ethiopia (32%) [27], among government employees in Mujja Town (37.6%) [30] and among civil servants' in Northwest Ethiopia (66.6%) [32]. But it found lower than the willingness and ability to pay for SHI in Nigeria (82%) [35] and among public servants in Mekelle City, Northern Ethiopia (85.3%) [24] In the nal multivariable logistic regression model, respondents who had higher educational level were 5.48(AOR = 5.48; 95% CI: 1.80, 16.73) times more likely to be willing to pay for SHI as compared to those teachers who were rst and diploma holders.…”
Section: Discussionsupporting
confidence: 66%
“…The OOP health expenditure in this study was much far away from WHO's target that health expenditure be viewed as catastrophic whenever it is greater than or equal to 40% of a household's non-subsistence income [29]. Higher level of awareness about SHI was seen in this study compared to other studies; 14.4% among government employee in Mujja town [30], 45% among Sodo town teachers [31], (47.3%) among civil servants' in Northwest Ethiopia [32], and 63% among healthcare providers in Addis Ababa [27]. But the awareness level of SHI in this study was less when compared with study in central Vietnam which was 91.8% [33] and 84.8% among health professional in Mekelle Town [26].…”
Section: Discussioncontrasting
confidence: 59%
“…The OOP health expenditure in this study was much far away from WHO's target that health expenditure be viewed as catastrophic whenever it is greater than or equal to 40% of a household's non-subsistence income [26,[27][28][29]. Higher level of awareness about SHI was seen in this study compared to other studies; 14.4% among government employee in Mujja town, 45% among Sodo town teachers, (47.3%) among civil servants' in Northwest Ethiopia, and 63% among healthcare providers in Addis Ababa [27,[30][31][32]. But the awareness level of SHI in this study was less when compared with study in central Vietnam which was 91.8% and 84.8% among health professional in Mekelle Town [26,33].…”
Section: Prevalence Of Willingness To Pay For Shi Among Public School...contrasting
confidence: 67%
“…The WTP for SHI was found to be influenced by sociodemographic factors like education level ( 20 22 , 25 , 31 , 32 ), income ( 17 , 19 21 , 27 , 28 , 31 , 34 ), age ( 26 , 28 , 31 ), marital status ( 28 , 33 ), occupation or job description ( 28 ), family size ( 29 , 30 , 34 ), and job experience ( 16 ); health and illness status such as self-rated healthiness ( 16 ), the presence of acute ( 20 , 21 , 31 ), and chronic illnesses ( 34 ); health service related factors like previous medical bills ( 16 , 18 , 21 , 22 , 24 , 27 , 28 , 30 , 35 ), referral system ( 26 ), regular medical checkup ( 26 ), and health service quality ( 16 , 19 , 24 – 27 ); awareness or knowledge ( 16 18 , 20 23 , 27 , 29 , 30 , 32 , 34 , 35 ); perception ( 24 , 31 ); attitude ( 17 , 21 , 27 , 33 , 34 ); and factors related to the scheme such as trust ( 17 , 23 ), premium amount ( 19 ), and the scope of the benefit packages ( …”
Section: Resultsmentioning
confidence: 99%